Unlocking the Potential of Pomelo Albedo: A Novel Substrate for Alpha-Amylase Production Using Bacillus licheniformis - Thi Ngoc Tran; Si-Chun Chen; Chien Thang Doan; San-Lang Wang (Fermentation, 2025)
The bioprocessing of agricultural wastes to produce microbial enzymes has become significant due to its benefits in reducing enzyme production costs and improving waste management. In this study, various substrates, including spent coffee grounds, coffee husks, coffee pulp, rice husks, rice bran, pomelo albedo, pomelo flavedo, orange peel, banana peel, sugarcane bagasse, and starch, were used as organic nutrient sources for α-amylase biosynthesis by B. licheniformis TKU004. Among the tested substrates, pomelo albedo (3%, w/v) was the most suitable carbon source for amylase production, with a productivity of 80.645 U/mL. The purification process resulted in a 60 kDa amylase. The protein identification of B. licheniformis TKU004 amylase revealed a coverage rate of 39% with α-amylase from Bacillus subtilis 168. B. licheniformis TKU004 amylase exhibited optimal activity at 60 °C and pH = 7 and showed a high compatibility with EDTA (Ethylenediaminetetraacetic acid). HPLC (high-performance liquid chromatography) analysis demonstrated that B. licheniformis TKU004 amylase is an α-amylase with the final products of maltobiose, maltose, and glucose. Due to its important properties, such as tolerance to EDTA, B. licheniformis TKU 004 amylase may be valuable for industrial applications, especially in detergents and food processing.